The Effectiveness of Reading and Writing Learning Videos on Student Learning Outcomes in Online Learning - Wibawa, I Made Citra; Dewi, Ni Putu Sri Ratna (International Journal of Elementary Education, 2022)
Online learning still faces many obstacles from teachers, students, and parents. One of the problems faced is lower-grade students' low learning outcomes reading and writing skills. This study aims to develop reading and writing learning videos for lower-grade students. This type of research is development research using the ADDIE model. The subjects of this study were 3 media experts, 3 material experts, and grade 1 students for the effectiveness test. The data collection method used is a questionnaire for validation and needs analysis, while the test is used for learning outcomes. The analytical method used is a qualitative method for needs analysis data and a quantitative method for validity and effectiveness testing. The results showed that the video learning to read and write deserved to be used in the outstanding category with a 4.44-4.81. effective reading and writing learning videos can improve student learning outcomes, and this is indicated by the t-test results obtained by the Sig score. < 0.05. So, reading and writing learning videos are feasible and effective to use in the learning process in lower-grade.